An Evaluation of Teacher Induction Program in Don Sergio Osmena Sr. Memorial National High School Through the Eyes of Beginning Teachers - Moral, Reynaldo; Zayas, Charlie (Universitas Terbuka, 2022)
The Department of Education, Division of Cebu City, Philippines, supports its Basic Education Learning Continuity Plan in the new normal. With the new trend of hiring new teachers, the Teacher Induction Program is one of the challenges ever faced by neophyte educators. This action research determined the challenges encountered by the beginning teachers during their Teacher Induction Program (TIP) in improving instructional effectiveness and professional development throughout the process. Using mixed methods of research design, the researchers administered survey questionnaires on their performances as well as a structured interview with the 12 novice teachers and conducted cross-validation for qualitative data analysis. Results showed that the Individual Performance Commitment Rating Form (IPCRF) has the highest rating (M= 4.0400) compared with their IPCRF Self-Rating (M= 3.7242) and TIP coordinator's rating (M= 3.7235). There is also a significant mean difference between the three mentioned variables (F= 4.36932) p-value is 0.02073, which leads to the rejection of Ho. However, the respondents are less serious when it comes to the challenges encountered in instruction, classroom management, and school location. Using Colaizzi’s Approach, 4 emerging themes surfaced: an Orderly Learning Environment; the Development of Effective Teaching Practices; Show Love, Respect, and Caring; and the Promotion of Personal and Professional Development. Based on the findings of the study, an enhanced mentoring program embedded in an action plan is recommended for reevaluating the TIP with the past induction efforts of the respondents, with stronger support from the school administrators.